A multicenter investigation of 2,773 cases of bloodstream infections based on China antimicrobial surveillance network (CHINET) - Hu, Fupin; Yuan, Lili; Yang, Yang; Xu, Yuanhong; Huang, Ying; Hu, Yunjian; Ai, Xiaoman; Zhuo, Chao; Su, Danhong; Shan, Bin; Du, Yan; Yu, Yunsong; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Bloodstream infections (BSIs), especially hospital-acquired BSIs, are a major cause of morbidity and mortality. However, the details about the pathogens and antimicrobial resistance profile of BSIs across China are still lacking. Methods An investigation was conducted in 10 large teaching hospitals from seven geographic regions across China in 2016 based on China Antimicrobial Surveillance Network (CHINET) to profile the clinical and etiological features of BSIs. Results A total of 2,773 cases of BSIs were identified, a majority (97.3%) of which were monomicrobial. Overall, 38.4% (1,065/2,773) were community-acquired BSIs (CABSIs), and 61.6% (1,708/2,773) were hospital-acquired BSIs (HABSIs). Of the 2,861 pathogenic BSI isolates, 67.5% were Gram-negative bacteria, 29.6% were Gram-positive bacteria, and 2.9% were fungi. The top BSI pathogens were Escherichia coli, Klebsiella pneumoniae, coagulase-negative Staphylococci (CNS), Staphylococcus aureus, Enterococci, and Acinetobacter baumannii. Escherichia coli and K. pneumoniae isolates showed low susceptibility to penicillins, cephalosporins (except ceftazidime and cefepime), and ampicillin-sulbactam (13.1%–43.4% susceptible); moderate susceptibility (about 60% susceptible) to ceftazidime, cefepime, and aztreonam; and high susceptibility (>90%) to β-lactam/β-lactamase inhibitor combinations other than ampicillin-sulbactam, except K. pneumoniae strains to piperacillin-tazobactam (59.2% susceptible). HABSIs were associated with significantly higher prevalence of carbapenem-resistant and extended-spectrum β-lactamases-producing K. pneumoniae, methicillin-resistant S. aureus, methicillin-resistant CNS, and ampicillin-resistant Enterococci than CABSIs. Overall, 42.0% of the BSI due to S. aureus strains were resistant to methicillin. Conclusions The findings about BSIs in teaching hospitals across China add more scientific evidence to inform the appropriate management of the disease.